Effect of hypoosmotic pressure on cell growth and antibody production in recombinant Chinese hamster ovary cell culture - Lee, Moon Sue (Kluwer Academic Publishers, 2001)
To determine the response of recombinant Chinese hamster ovary (rCHO) cells subjected to hypoosmotic pressure, rCHO cells (CS13*–1.0) producing a chimeric antibody were cultivated in the hypoosmolar medium resulting from NaCl subtraction. At hypoosmotic pressure, CS13*–1.0 cells displayed decreased specific growth rate (μ) and increased specific antibody productivity (q(Ab)).When the medium osmolality was decreased from 300 mOsm kg(-1)(physiological osmolality) to 150 mOsm kg(-1), μ was decreased by 68% and q(Ab) was increased by 128%. To understand the mechanism of enhanced q(Ab) resulting from hypoosmotic pressure, cellular responses of cells in the exponential phase of growth were observed at the transcription level. Total cytoplasmic RNA content per cell at 150 mOsm kg(-1) was increased by 140%, compared with that at 300 mOsm kg(-1). On a per μg RNA basis, immunoglobulin (Ig) mRNA levels at 150 mOsm kg(-1) were comparable to those at 300 mOsm kg(-1), indicating that hypoosmotic pressure did not lead to the preferential transcription of Ig mRNAs. Taken together, the data obtained here suggest that the increase in total RNA pool is primarily responsible for the enhanced q(Ab) of CS13*–1.0 cells subjected to hypoosmotic pressure.